MENINGKATKAN MINAT DAN HASIL BELAJAR SENI BUDAYA DENGAN BERBASIS MEDIA CANVA PADA PESERTA DIDIK KELAS X BDPM 2 DI SMKN 2 DENPASAR - Dina Pujipebrianti Lestari; I Ketut Muada (CV. ADIBA AISHA AMIRA, 2023)
This classroom action research aims to increase the interest and learning outcomes of class X BDPM 2 students at SMKN 2 Denpasar in the subject of cultural arts management of collaborative dance performances using the Project Based Learning (PBL) method with Canva media. Student interest and learning outcomes are low because of the lack of teacher skills in applying interesting learning media and the lack of student involvement in learning. The study was conducted in two cycles and involved group project assignments in the management of dance performances with data analyzed using descriptive statistical techniques. The results show that the implementation of PBL with Canva media significantly increases students' interest and learning outcomes in arts and culture. It is suggested that teachers use this method to promote active, creative, and fun learning experiences for their students. The average score of student learning outcomes increased from 68.57 in the pre-test to 87.50 in the post-test, while student interest increased from 3.00 to 3.69 on a 5-point Likert scale. Therefore, PBL with Canva media can be used as an effective method to increase student interest and learning outcomes in arts and culture, especially in managing group dance performances.